A six-week neuromuscular training program for competitive junior tennis players - Barber-Westin, S. D.; Hermeto, A. A.; Noyes, F. R. (The Journal of Strength and Conditioning Research, 2010)
This study evaluated the effectiveness of a tennis-specific training program on improving neuromuscular indices in competitive junior players. Tennis is a demanding sport because it requires speed, agility, explosive power, and aerobic conditioning along with the ability to react and anticipate quickly, and there are limited studies that evaluate these indices in young players after a multiweek training program. The program designed for this study implemented the essential components of a previously published neuromuscular training program and also included exercises designed to improve dynamic balance, agility, speed, and strength. Fifteen junior tennis players (10 girls, 5 boys; mean age, 13.0 ± 1.5 years) who routinely participated in local tournaments and high-school teams participated in the 6-week supervised program. Training was conducted 3 times a week, with sessions lasting 1.5 hours that included a dynamic warm-up, plyometric and jump training, strength training (lower extremity, upper extremity, core), tennis-specific drills, and flexibility. After training, statistically significant improvements and large-to-moderate effect sizes were found in the single-leg triple crossover hop for both legs (p < 0.05), the baseline forehand (p = 0.006) and backhand (p = 0.0008) tests, the service line (p = 0.0009) test, the 1-court suicide (p < 0.0001), the 2-court suicide (p = 0.02), and the abdominal endurance test (p = 0.01). Mean improvements between pretrain and posttrain test sessions were 15% for the single-leg triple crossover hop, 10-11% for the baseline tests, 18% for the service line test, 21% for the 1-court suicide, 10% for the 2-court suicide, and 76% for the abdominal endurance test. No athlete sustained an injury or developed an overuse syndrome as a result of the training program. The results demonstrate that this program is feasible, low in cost, and appears to be effective in improving the majority of neuromuscular indices tested. We accomplished our goal of developing training and testing procedures that could all be performed on the tennis court.